Discrete Time Two-Frequency Shift Keying - Paramote Wardkein; Chanapat Kaew-in; Thanaree Wanprasert; Pandaree Philuek; Nateekan Moonthongnoi; Peeramed Chodkaveekityada (My University, 2024)
In this article, two-frequency shift keying is used to modify the time for generating the Time-Frequency Shift Keying (TFSK). Which both frequencies occupy different times and vary with a message. For this mechanism, it causes M-ary time-frequency pattern coding, where one pattern can code n bits if we have different ${2}^n$ patterns, which overall code like a Pulse Width Modulation (PWM) combined with binary FSK. To confirm the proposed idea or technique, four-time-frequency coding is simulated with MATLAB, and an experiment is implemented with a commercial FSK IC. Both simulations and experimental results show that they are identical to predictions. Moreover, its bandwidth is predicted, and clock recovery is also implemented.
Keywords: Molecular Communication and Nanonetworks; Cooperative Communication and Network Coding; Energy Harvesting in Wireless Networks